Microbiological and clinical epidemiology of cryptococcosis in non-HIV Korean patients: 4-year collection - Bosung Park; Eunsang Suh; Yeseul Choi; Tae Yeul Kim; Eun Jeong Won; Hee Jae Huh; Heungsup Sung; Mi-Na Kim (Journal of Infection and Public Health, 2025)
Background: Cryptococcosis causes a high burden of disease worldwide; however, it has been relatively rare in Korea, where data on its prevalence and clinical characteristics remain limited. This study aimed to characterize the microbiological features of clinical cryptococcal isolates and to investigate the clinical profiles of HIV-negative patients with cryptococcosis in South Korea. Methods: Clinical isolates of Cryptococcus species were collected from two university hospitals in South Korea (about 5000 beds, in total) over a 4-year period. Species identification, multilocus sequence typing, and antifungal susceptibility testing were performed. Clinical features of cryptococcosis and prognostic factors for 30-day mortality were analyzed by univariate and multivariate logistic regression analysis. Results: A total of 40 nonduplicate isolates from 39 patients during the study period and sequencing confirmed 38 isolates of C. neoformans and 2 isolates of C. deuterogatii. MLST analysis of C. neoformans identified 35 isolates as ST5, along with single isolates of ST2, ST15, and a newly discovered sequence type, ST707. The percentages of non-wild type to amphotericin B, 5-fluorocytosine, fluconazole, itraconazole, voriconazole, and posaconazole were 10.0 %, 4.0 %, 8.0 %, 6.0 %, 2.0 %, and 8.0 %, respectively. However, the two isolates of C. deuterogatii exhibited a wild type phenotype for all the aforementioned antifungal agents. Overall, the cumulative 30-day mortality rate was 41.0 % (16/39). Univariate analysis showed that total parenteral nutrition, severe sepsis, intensive care unit admission, vasopressor use, acute renal failure, and underlying chronic kidney disease (CKD) were risk factors for 30-day mortality, and azole therapy was the protective factor. Finally, CKD was the independent risk factor for 30-day mortality by multivariate analysis. No significant differences were observed in patient survival across sequence type of isolates. Conclusions: This study showed that ST5 was the predominant genotype of C. neoformans in South Korea and CKD significantly increased the risk of 30-day mortality of cryptococcosis.